The effect of rabbit skeletal muscle on the large segment autologous bone ectopic preconstruction of vascularized bone flap - Li, Yanfeng; Zhou, Mingwu; Shi, Qiyun; Chen, Da (Frontiers in Bioengineering and Biotechnology, 2025)
Aim of the studyTo investigate the spatiotemporal secretion patterns of vascular endothelial growth factor (VEGF) and bone morphogenetic protein-2 (BMP-2) in rabbit skeletal muscle and their effects on the ectopic prefabrication of vascularized osteocutaneous flaps using large-segment autologous bone grafts.MethodsSeventy adult Chinese white rabbits (gender-neutral) were randomly assigned: 60 rabbits to the experimental group and 10 to the blank control group. In the experimental group, a 1.5 cm midshaft tibial segment from the left hindlimb was aseptically excised, stripped of soft tissues from the medullary cavity and bone surface, sterilized via high-temperature water bath, and implanted into the right rectus femoris muscle pouch for flap prefabrication. The control group underwent harvesting of a 1.5 cm left tibial midshaft segment and the entire right rectus femoris muscle without implantation. At 2, 4, 6, 8, 10, and 12 weeks postoperatively, 10 rabbits in the experimental group were euthanized to harvest the large-segment autologous bone and intact rectus femoris muscle. Specimens were analyzed for: 1. Macroscopic observation of bone remodeling; 2. Histological examination via hematoxylin-eosin (H&E) staining; 3. Immunofluorescence staining for CD34 (vascularization marker) and type I collagen (bone activity marker); 4. Western blotting to quantify VEGF and BMP-2 expression in muscle tissue. The control group was evaluated using identical methods.Results1. Macroscopic Observation. The experimental group exhibited uneventful wound healing without inflammation. Fibroconnective tissues at the medullary cavity ends and bone cortex surface gradually thickened and adhered tightly over time. Upon dissection, increased number and depth of bone resorption lacunae and thinning of the bone cortex were observed. By week 8, the fibroconnective tissues wrapping the bone segment mimicked the thickness and tightness of the native periosteum, showing resistance to separation. 2. Histological Analysis (H&E Staining). Progressive bone tissue repair was observed in the experimental group: Week 2: Minimal fibrous granulation tissue on the bone surface and within the lumen. Week 4: Emergence of fibrous granulation tissue with sparse neovessels and cellular components. Week 6: Increased vascularity and cellularity, regular arrangement of bone vortices adjacent to blood vessels, appearance of mature osteocytes, expanded Haversian canals, and initiation of trabecular bone growth. From week 8 onward: Histological features matched fresh tibia, showing abundant vascular endothelial cells, osteocytes, and dense mature bone trabeculae. 3. Immunofluorescence Detection. CD34-positive blood vessels: The experimental group showed a “rise-then-slow-decline” trend, peaking at week 8 with significantly increased counts at each time point from week 2–8 compared to the prior week (P < 0.05). Compared to the experimental group at weeks 2, 4, 6, and 12, the baseline CD34-positive vessel number in the control group was significantly higher (P < 0.05). Type I collagen fluorescence intensity: An initial increase followed by a decline was observed in the experimental group, peaking at week 10 with significant enhancement from week 4–10 compared to the prior week (P < 0.05). Compared to the experimental group at weeks 2, 4, 6, and 12, the baseline Type I positive vessel number in the control group was significantly higher (P < 0.05). 4. Cytokine Secretion in Rectus Femoris Muscle. VEGF: Secretion in the experimental group followed an “increase-plateau-decrease” pattern, peaking at weeks 4–6 (significantly higher than weeks 2, 8, 10, and 12, P < 0.05) and exceeding control levels at weeks 2, 4, 6, and 8 (P < 0.05). BMP-2: Secretion peaked at week 6 (significantly higher than weeks 2, 8, 10, and 12, P < 0.05), being higher than the control group at weeks 2, 4, 6, and 8 (P < 0.05) but lower at weeks 10 and 12 (P < 0.05).Conclusion1. During the ectopic prefabrication of vascularized osteocutaneous flaps using large-segment autologous bone, rabbit skeletal muscle secretes VEGF and BMP-2 in a spatiotemporally regulated manner. 2. VEGF and BMP-2 exhibit early-phase upregulation followed by gradual decline, playing critical roles in the prefabrication process. 3. Skeletal muscle promotes concurrent angiogenesis and enhanced bone activity during flap prefabrication. Completed vascularization at week 8 further supports sustained bone activity, facilitating functional bone regeneration.